Examining the Role of Teachers’ Stroking Behaviors in EFL Learners’ Active/Passive Motivation and Teacher Success - Pishghadam, Reza; Derakhshan, Ali; Jajarmi, Haniyeh; Tabatabaee Farani, Sahar; Shayesteh, Shaghayegh (Frontiers in Psychology, 2021)
Due to the important role that teachers’ professional success plays in the effectiveness of their students and the education system in which they are involved, the present study investigated whether teacher stroke can predict teacher success through the mediation of students’ active and passive motivation. For this aim, a group of 437 Iranian university English as a Foreign Language (EFL) students were targeted to respond to the teacher success, teacher stroke, and student motivation questionnaires. The main results of the study, obtained through running correlation and structural equation modeling (SEM), were first, while positive stroke showed a positive correlation with teacher success, it did not directly predict success; yet mediated by active motivation, it was a positive predictor of success; second, while teacher success had no significant relationship with total motivation, it was positively correlated with active and passive motivation, separately; third, in terms of gender differences, for the female participants, stroke, mediated by active motivation, was a better predictor of teacher success; fourth, high scores in positive, verbal, and conditional stroke were in association with high scores in active motivation, which significantly predicted teacher success. Based on the results, it can be concluded that teacher stroke, as an instance of positive teacher interpersonal communication behaviors, increases students’ active motivation for foreign language learning, which in turn results in their higher perceptions of English teachers’ professional success.